2020
DOI: 10.1155/2020/8883316
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Stakeholder Relation Network of the Qingdao Elderly Livable Community Construction Project

Abstract: Due to the population ageing, building an elderly livable community has become an urgent task of social welfare development. This Public-Private Partnership construction project faces a variety of pressures from its complex stakeholders. Based on the Qingdao elderly livable community construction project, this paper builds up interpretations about its relationship governance by conducting stakeholder analysis. The paper aims to explore the relationship governance mechanism of multiple connections between relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Regarding InDegre, the values of A1ENAMI [12] and A6SEREM ÍA [10] are relatively high, indicating that both institutions are ones that contact more actors to deal with extraction problems. e results of both centralities give us a first idea about the strategy to be implemented considering the contact power of the triad A1, A6, and A11.…”
Section: Power Quantification Analysis Of Chilean Small Miners'mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding InDegre, the values of A1ENAMI [12] and A6SEREM ÍA [10] are relatively high, indicating that both institutions are ones that contact more actors to deal with extraction problems. e results of both centralities give us a first idea about the strategy to be implemented considering the contact power of the triad A1, A6, and A11.…”
Section: Power Quantification Analysis Of Chilean Small Miners'mentioning
confidence: 99%
“…In this way, promoting new ways of cooperation between the different actors could correct the negative impacts caused by the influence of a few actors. e complex network method can be used to study this kind of complex structural relation among these stakeholders, in which there are different individuals with a large number of interactions [12].…”
Section: Introductionmentioning
confidence: 99%
“…An assessment was conducted, which indicated that the NRPS has improved old-age services for the elderly in the western region and that an increase in NRPS payments is considered necessary [19]. Dong, M. and other researchers analyzed the Qingdao senior livable community to study the governance mechanism of complex interests, and the results of the study showed that the cooperation between the government and the capital to build the senior living community can help to alleviate the financial pressure, but it needs to be very attentive and cautious about the complex interests [20]. Xu, Y. W. Y. constructed a smart, safe, and reliable evaluation index system for the quality of smart community pension services to guarantee the services of smart pensions, and took four cities in Jiangsu Province as the research object to test the proposed evaluation method, and the test results confirmed the feasibility and reliability of this method, and the above research helps to standardize the pensioned services [21].…”
Section: Introductionmentioning
confidence: 99%
“…Te factors contributing to the aforementioned delay were the inadequate legal basis, deviation of the executive body, incomplete management system, imperfect supervision mechanism, outdated concept of aging development, unequal basic rights, limited diversity of choices, insufcient educational empowerment, human development awareness, and educational stratifcation [8]. Previous studies have investigated the problems and factors that have infuenced the developmental stages of China's elderly education policy, such as policy formulation, policy development and variation, and policy implementation, and have provided valuable recommendations regarding the framework and implementation of the policy system [9]. To a certain extent, these studies can help policymakers formulate more efective policies for education for the elderly.…”
Section: Introductionmentioning
confidence: 99%